2017
DOI: 10.1186/s40360-016-0108-3
|View full text |Cite
|
Sign up to set email alerts
|

5-aminolevulinic acid combined with ferrous ion reduces adiposity and improves glucose tolerance in diet-induced obese mice via enhancing mitochondrial function

Abstract: BackgroundMitochondrial dysfunction is associated with obesity and various obesity-associated pathological conditions including glucose intolerance. 5-Aminolevulinic acid (ALA), a precursor of heme metabolites, is a natural amino acid synthesized in the mitochondria, and various types of cytochromes containing heme contribute to aerobic energy metabolism. Thus, ALA might have beneficial effects on the reduction of adiposity and improvement of glucose tolerance through its promotion of heme synthesis. In the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
36
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(46 citation statements)
references
References 39 publications
9
36
1
Order By: Relevance
“…An increase of heme turnover following an increase of ALAS is associated with a reduction of adiposity, increased mitochondrial function and adipocyte function [56], [57]. These results are in agreement with this report that HO-1 deletion results in a decrease in heme turnover and PGC1α, the latter is essential to restore mitochondrial integrity and increase beige like cells.…”
Section: Discussionsupporting
confidence: 92%
“…An increase of heme turnover following an increase of ALAS is associated with a reduction of adiposity, increased mitochondrial function and adipocyte function [56], [57]. These results are in agreement with this report that HO-1 deletion results in a decrease in heme turnover and PGC1α, the latter is essential to restore mitochondrial integrity and increase beige like cells.…”
Section: Discussionsupporting
confidence: 92%
“…In mice, administration of 5‐ALA was previously reported to increase the ATP level in the liver (Ogura et al., ) and the expression and activity of respiratory cytochromes in the mitochondrial electron transport chain (Ogura et al., ; Ota et al., ). This result is similar to our current results in which the ATP level in the hepatopancreas of L. vannamei was higher in the 5‐ALA groups than in the control (Figure ), in a dose‐dependent manner.…”
Section: Discussionmentioning
confidence: 96%
“…Several studies of vertebrates and vertebrate cell lines support the hypothesis that exogenous 5‐ALA enhances haem synthesis and activity of haemoproteins: 5‐ALA administration (a) increased intracellular haem levels, increasing the activity of cytochrome P450 in vitro (Miura et al., ); (b) increased the activity of cytochrome c oxidase of the electron transport chain and raised ATP levels in mouse liver (Ogura et al., ); (c) enhanced protein expression of mitochondrial complexes III–V in mouse adipose tissue (Ota et al., ); (d) induced REV‐ERBα expression (Yamashita et al., ); and (e) induced both protein and mRNA expression of haem oxygenase‐1 (HO‐1) (a rate‐limiting enzyme in haem degradation) (Nishio et al., : Ito et al., ). 5‐aminolevulinic acid was also reported to enhance the immune response in chickens (Sato et al., ) and pigs (Chen et al., ) and improves growth performance in eels (Yasumoto, Miyanari, Yoshimura, Kondo & Takahashi, ) (although there is some disagreement on the effect of 5‐ALA on growth; see below).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Since ALA causes tumour accumulation of protoporphyrin IX, it has already been used as an oral diagnostic drug for cancer in Japan, Europe, Australia, and Canada 2,3 . We previously reported that ALA supplementation in mice enhances cytochrome c oxidase (COX) activity and ATP production levels in liver, and ALA combined with sodium ferrous citrate (SFC) administration upregulates the expression of OXPHOS complexes III, IV, and V in white adipose tissues of diet-induced obese mice, resulting in reduced lipid content of adipocytes 4,5 . Furthermore, ALA combined with SFC in healthy humans increased the expression levels of haem oxygenase-1 (HO-1) in peripheral blood mononuclear cells, which has cytoprotective effects against oxidative stress and inflammation 6,7 .
Figure 1Haem biosynthesis pathway.
…”
Section: Introductionmentioning
confidence: 99%